Analytical solutions of 2-D problem for cracked thermoelastic fiber-reinforced anisotropic material. (October 2017) - Abbas, Ibrahim A.
Highlights: 2D thermoelastic interaction in a fiber-reinforced material is established. The boundary of the crack is subjected to a prescribed stress and temperature. The analytical solution is investigated by the eigenvalue approach techniques. Fiber-reinforced material properties act to reduce the magnitudes of all variables. The visualization of the mechanics of crack growth under loading is presented. Abstract: In this article, the analytical solution of the 2D problem for cracked thermoelastic fiber-reinforced anisotropic material is investigated. The boundary of the crack is due to a prescribed temperature and stress distribution. In the case of one relaxation time, the generalized thermoelastic theory has been employed. In the transformed domain using exponential Fourier and Laplace transformations, the eigenvalues approach are used to obtain the analytical solutions. The inverse of Fourier transform has been obtained analytically. Comparisons with expected results by the absence and presence of reinforcement have been presented. Results were verified numerically and are represented graphically.